The Acceptability Level of Bitter Melon Leaves Pandesal Among Grade 12 Students of Home Economic Strand in Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
One of the most popular breads in the Philippines is “Pandesal,” which Filipinos regularly eatas comfort food in the morning. They frequently dip the bread in coffee or stuff it with cheese,eggs, peanut butter, and other ingredients. Many kids don't like the flavor of bitter melon,which makes them despise the bitter vegetable. But as people age, their palates change,which is why older people like bitter melon vegetables. One of the most well-known Filipinorecipes, pinakbet, uses bitter melon, or ampalaya. Even in its bitterness, its health-givingproperties will remain.The results stated that using Bitter melon leaves in Pandesal to make the product achievedthe expectation. There’s no significance between the assessments of the respondent as aforecited variable. Wash and dry the bitter melon leaves to reduce the bitterness itself.Respondents assessed the level of acceptability of the product in terms of taste asSatisfactory, texture, appearance, similarity, and rate as satisfactory.In this study, researchers discussed how bitter melon leaves are an ideal addition to pandesal.Since many children and adults dislike bitter melon due to its bitter taste, they frequently missout on important nutrients like vitamins A and C and iron. In order to minimize the bitterness ofbitter melon leaves without reducing the fruit's nutritional value, researchers came up with away to wash and dry the leaves. By soaking bitter melon leaves in the water to remove the dirtand insects and drying them using the oven or directly in the sun, without removing thenutrients in the leaves. Researchers also made certain that the dough was sweet enoughbefore baking in order to avoid the strong bitterness of the pandesal.
Keywords: Hotel and Restaurant Management